Outbreak conditions and impacts of parasites in copepod populations - Even Sletteng Garvang; Lasse Krøger Eliassen; Josefin Titelman; Tom Andersen (Ecosphere)
Abstract Although parasitism is vital for ecosystem dynamics and food webs, the population effects of parasitism in the marine pelagic have received little attention. Pelagic copepods link primary producers and higher consumers in marine food webs and host numerous parasites that may affect reproduction, behavior, and survival. We present a simple model consisting of uninfected hosts, infected hosts, and the free‐living parasite stage and use it to investigate population dynamics and outbreak conditions of this host–parasite system. The host population growth is limited by a carrying capacity determined by resource availability and stoichiometric constraints. We parameterized the model for 10 copepod species with different traits but with the same Blastodinium‐like parasite. We derived a threshold ratio R0 for establishing infection, which showed that the parasite could invade and persist in all hosts. The ability of parasites to invade host populations largely depended on traits of free‐living spores and host density. From numerical analysis, we found that the parasite typically induced oscillations in the host population. Host traits were important for infection dynamics: High host growth rates mitigated some of the consequences of infection, and larger copepods were more susceptible to infection than smaller ones. The model implies that parasitism can impact the functional role of the copepod population in the ecosystem, and the system as a whole.